Functional Analysis of a Coding Variant In ZC3HC1 at 7q32.2 Associated with Protection Against Coronary Artery Disease (CAD) - Linseman, Tara (Université d'Ottawa / University of Ottawa, 2016)
Coronary artery disease (CAD), characterized by the narrowing of coronary arteries through the complex manifestation and development of atherosclerosis, is a complex disease and one of the leading causes of death worldwide. Both genetic and environmental factors are believed to contribute equally to the risk of CAD. Recently, a study identified a non-synonymous coding variant, rs11556924, (MAF, 0.38) in ZC3HC1 associated with protection against CAD (p= 9.8x10-18; OR= 0.90). NIPA, encoded by ZC3HC1, is a characterized F-Box protein and regulator of cell cycle. Since the amino acid change (Arg363His) is in a conserved region of NIPA and is predicted to have functional effects (Polyphen-2), this study aimed at understanding the functional implications of this amino acid change on NIPA and cell cycle regulation. Here we are able to effectively show a) allele specific differences in mRNA expression in whole blood, b) a slight structural difference between NIPA363Arg and NIPA363His variants, c) proliferation rates of NIPA363Arg expressing cells were significantly increased, and d) phosphorylation of a critical serine residue in close proximity to aa.363 is not statistically different between the two variants. These results suggest that rs11556924 plays a direct role in development of CAD through its disruption of cell cycle regulation and NIPA mRNA availability. This study is the first to identify a molecular basis for the association of rs11556924 to CAD development.
Keywords: Cell Cycle; CAD; Genetics; Protein